HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP ANAK PENDERITA THALASEMIA DI RS BHAYANGKARA - Nabila Budiarti; Johan Budhiana; Iyam Mariam (JURNAL KESEHATAN INDRA HUSADA, 2022)
Thalassemia is a chronic disease in children that affects the quality of life. The purpose of this study was to determine the relationship between family support and the quality of life of school-age children with thalassemia. School age children are children aged 6-12 years. Thalassemia is a blood disorder caused by genetic factors. Family support is a form of encouragement, assistance received by individuals from parents or family members. Quality of life is an individual's perception of his position in life. Types of correlational research. The population of all school-age children who suffer from thalassemia with a sample of 45 respondents. Sampling uses total sampling. Data collection techniques with questionnaires. Bivariate analysis using Fisher's exact test. The results showed that most of them had good family support and had a good quality of life. Fisher's exact test results obtained p-value = 0.027. The conclusion shows that there is a relationship between family support and the quality of life of school-age children with thalassemia. It is hoped that Bhayangkara Hospital can maintain and motivate families regarding the importance of family support through health education.